2020
DOI: 10.3390/s20144039
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Evaluation of Red Blood Cells of Thalassemia Patients with Confocal Microscopy: A Pilot Study

Abstract: Hemoglobinopathies represent the most common single-gene defects in the world and pose a major public health problem, particularly in tropical countries, where they occur with high frequency. Diagnosing hemoglobinopathies can sometimes be difficult due to the coexistence of different causes of anemia, such as thalassemia and iron deficiency, and blood transfusions, among other factors, and requires expensive and complex molecular tests. This work explores the possibility of using spectral confocal microscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Another problem is the fact that the emission spectra of RFP compete (to some extent) with the autofluorescent signal from animal tissues. Components such as collagen or red blood cells are strongly autofluorescent, making a background noise that needs to be distinguished from the signal emitted by RFP-labelled phage [ 33 , 34 ]. For this reason, in the presented experiments, the background signal in control organs (excised from animals not treated with the RFP phage) was detectable.…”
Section: Discussionmentioning
confidence: 99%
“…Another problem is the fact that the emission spectra of RFP compete (to some extent) with the autofluorescent signal from animal tissues. Components such as collagen or red blood cells are strongly autofluorescent, making a background noise that needs to be distinguished from the signal emitted by RFP-labelled phage [ 33 , 34 ]. For this reason, in the presented experiments, the background signal in control organs (excised from animals not treated with the RFP phage) was detectable.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency or severity of bleeding was verified by measuring the total number of red blood cells (RBCs) detected in the tissue section. As RBCs exhibit autofluorescence ( 31 ), the false-colored yellow signal that produced by coexpression at 470- and 530-nm wavelengths was defined as autofluorescence produced by RBC. Ten areas of the liver were randomly selected from each mouse, and the dimension ratio of the yellow fluorescence signal was quantified.…”
Section: Resultsmentioning
confidence: 99%
“…Hemoglobinopathies are common, particularly in tropical countries, but their diagnosis can be difficult due to alternative causes of anaemia resulting in expensive genetic tests. Rey‐Barroso et al found that red blood cells from patients with different forms of alpha‐thalassemia, iron deficiency (including iron deficiency anaemia), and healthy controls could be discriminated using a multispectral confocal system with excitation at 405 nm and emissions collected from 452 to 791 nm in 7 nm steps [57]. Specifically, mean intensities at 502, 579, 628 and 649 nm allowed full differentiation of diseased and healthy cells.…”
Section: Blood Diseasesmentioning
confidence: 99%